Premenopausal Trabecular Bone Loss is Associated with a Family History of Fragility Fracture - Prior, J. C.; Hitchcock, C. L.; Vigna, Y. M.; Seifert-Klauss, V. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Although a fragility fracture family history (FFFH+) has repeatedly been shown to be associated with lower bone mineral density (BMD), its relationship to human BMD change is unclear. Animal research, however, documented that different purebred strains within rodent species have wide ranges in rates of bone acquisition during growth as well as in change post-ovariectomy. Our objective was to compare the rate of premenopausal spinal trabecular BMD change between women with and without a general family history of fragility fracture. Participants and Methods: Healthy premenopausal community women participated in prospective observational studies at two academic medical research centres: Vancouver, Canada (n = 66) and Munich, Germany (n = 20). The primary outcome was annual spinal BMD change, measured by quantitative computed tomography (QCT). The two studies employed similar methodologies for assessing QCT and FFFH. Results: Volunteer community participants had a mean age of 36.0 (SD, 6.9) years, body mass index 22.5 (2.4) and baseline QCT of 150.2 (22.5) mg/cm3 trabecular bone. The rates of BMD change were similar in both cities: − 3.5 (5.1)/year Vancouver, − 2.0 (3.4)/year Munich (95 % CI of difference: − 3.9, 0.9). Over a third of the women (31 of the 86, 36 %) reported FFFH+. Those with and without a FFFH were similar in demographics, nutrition, exercise, menstrual cycle and luteal phase lengths and physiological measures (serum calcium, osteocalcin and estradiol). However, women with FFFH+ lost trabecular BMD more rapidly: FFFH+, − 4.9 (5.0), FFFH−, − 2.2 (4.4) mg/cm3/year (95 % CI diff − 0.7 to − 4.8, F1.83 = 7.88, p = 0.006). FFFH+ explained 7.7 % of the variance in QCT volumetric trabecular spinal bone change/year in these healthy premenopausal women. Conclusion: This study shows for the first time that having a history of a fragility fracture in a family member is associated with a greater rate of premenopausal spinal trabecular bone loss.
Keywords: osteoporosis; QCT; bone turnover; menstrual cycle; estrogen; genetics